Electro osmosis irrigation - ANILA JOSEPH MORRIS; Binu Koshy; Jasmine Davis; Er. Abdul Hakkim V. M (Guide) (Tavanur 1999 department of irrigation)
Electro osmosis irrigation
Electro osmosis irrigation